2022
DOI: 10.3390/cancers14040950
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Resolution Dedicated PET-Based Radiomics Machine Learning Model to Predict Axillary Lymph Node Status in Early-Stage Breast Cancer

Abstract: Purpose of the Report: Accurate clinical axillary evaluation plays an important role in the diagnosis and treatment planning for early-stage breast cancer (BC). This study aimed to develop a scalable, non-invasive and robust machine learning model for predicting of the pathological node status using dedicated-PET integrating the clinical characteristics in early-stage BC. Materials and Methods: A total of 420 BC patients confirmed by postoperative pathology were retrospectively analyzed. 18F-fluorodeoxyglucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…In our previous study, we developed a machine learning model integrating LymphPET and clinical characteristics for the prediction of axillary LN status in cT1-2N0-1M0 breast cancer. The performance of this integrated model showed an NPV of 96.88% in the cN0 subgroup; therefore, we believe that the use of a machine learning integrated model can greatly improve the true positive and true negative rates of identifying clinical axillary LN status in early-stage BC 22 .…”
Section: Discussionmentioning
confidence: 87%
“…In our previous study, we developed a machine learning model integrating LymphPET and clinical characteristics for the prediction of axillary LN status in cT1-2N0-1M0 breast cancer. The performance of this integrated model showed an NPV of 96.88% in the cN0 subgroup; therefore, we believe that the use of a machine learning integrated model can greatly improve the true positive and true negative rates of identifying clinical axillary LN status in early-stage BC 22 .…”
Section: Discussionmentioning
confidence: 87%
“…They found that SVM outperformed visual assessment for this purpose (0.77 vs. 0.89, 0.57 vs. 0.94, 0.77 vs. 0.77 and 0.71 vs. 0.85, for AUC, sensitivity, specificity, and accuracy, respectively). Cheng et al [ 42 ] aimed to develop a ML model combining dbPET features and clinical variables to predict pathological involvement of ALN in 420 early-stage BC. The AUC of the integrated model, which included six clinical-pathological factors and five dbPET radiomics parameters, was 0.94 in the training set (n = 203) and 0.93 in the validation set (n = 87) ( p < 0.05 in both cases).…”
Section: Resultsmentioning
confidence: 99%
“…Many scholars had applied Ultrasound, MRI, and PET-CT images to carry out radiomics studies [23][24][25], involving radiomics and clinical features to lymph node metastasis of breast cancer. In particular, LNM radiomics studies of tumors (pancreatic ductal adenocarcinoma, gastric cancer, cervical cancer, etc.)…”
Section: Discussionmentioning
confidence: 99%